An examination of user generated content value on culturally based consumer groups - Chen, Zhiyang (Kansas State University, 2013)
The consumer value of user generated content was investigated between culture groups. Two groups of survey participants and three groups of interview respondents were utilized to identify the culture value’s influence on people’s reliance and preference in consumption-related UGC information. The behavior pattern of Chinese students and American students on UGC were identified and connected with dimensions of culture value. Some difference in preference and attitude between Chinese users and American users were found in this research. Power distance, individualism, and uncertainty avoidance are considered important cultural factors that influence the consumer-value of UGC in each culture group. Several potential areas for future quantitative and qualitative study as well as suggestions for UGC platform providers were also identified.
Keywords: Culture, values; User generated content; Social media; Americans; Chinese; Mass Communications (0708)